Design of a Lift Bridge Model on a Navigable River Using an Microkontroler ATMEGA 8 - aditiarno manik; Jorro Manalu (Jurnal ICT : Information and Communication Technologies, 2021)
Today's technology has developed rapidly and rapidly, especially in the field of control electronics. However, the current transport bridge control system in Indonesia is still underdeveloped. The mindset of the Indonesian people tends to deify foreign products. The practicality of bringing in a tool and just installing the tool is one of the causes of the underdevelopment of the transport bridge control system in this country. Actually, Indonesian citizens are able to make these tools, especially since Indonesia is an archipelagic country and still uses water transportation facilities. Based on this in this final project, a miniature lift bridge simulation was designed and made using an ATMEGA 8 microcontroller. Supporting components so that the miniature lift bridge control system can work according to the desired design, including the ATMEGA 8 microcontroller as a data controller that changes the LED lights, and moves the servo motor to lift or close the bridge, when the ship hits the infrared sensor. From the results and analysis, it is found that the output voltage produced by the circuit is 5 volts, and the speed of the ship so that the sensor can be detected should not be more than 2.6 cm/s.